Debunking the myth of the 'mentally ill' mass shooter. Issue 35 (9th September 2022) - Pollock, Michael
Abstract : The Depression and Bipolar Support Alliance (DBSA) acknowledges the heaviness that many people around the country are feeling in the wake of the mass shootings at Robb Elementary School in Uvalde, Texas, and Saint Francis Hospital in Tulsa, Oklahoma, which, sadly, follow on the heels of shooting incidents earlier this year in Buffalo, Dallas, and Los Angeles.